(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Nature has been a source of medicinal agents for more than thousands of years and herbal therapy predominates in traditional systems of medicine as well as in alternative medicine practiced in various cultures such as Indian system of medicine, Chinese Traditional Medicine, Unani classical literature. The present review deals with various polyherbal formulations used by different countries of the world. Information on traditional herbal formulations was documented in the form of research and review articles in various journals. The aim of this review is to summarize the different types of herbs used for the preparation of polyherbal formulations, their therapeutic potentials including clinical and preclinical results along with their safety and efficacy. This review will facilitate to gain all about the past scientific research and the necessary information about the enormous pharmacological activities of polyherbal formulations which will insist the young researchers for future research to protect human beings from various types of diseases and may serves as a natural gold for the promotion of mankind.